Psychological Contract Breach, Abusive Supervision, and Turnover Intention among Nigerian Healthcare Workers: Examining the Mediating Role of Organizational Cynicism - Anthony G. Balogun; John M Elisha; Emmanuel E Uye (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Nigeria is currently facing a significant shortage of qualified healthcare professionals. With forecasts suggesting that the population could reach 263 million by 2030 and a growing trend of medical practitioners leaving the country, this challenge is expected to worsen unless addressed effectively. Utilizing social exchange theory, this study explored the relationship between psychological contract breach, abusive supervision, and the turnover intentions of healthcare workers in Nigeria, as well as, investigating the mediating effect of organizational cynicism in these relationships. A cross-sectional survey design was employed to collect data from a sample of 200 healthcare professionals in tertiary and secondary public hospitals across the three senatorial districts in Ondo State, Nigeria. The findings revealed that both psychological contract breach and abusive supervision were positively correlated with turnover intentions among this group. Furthermore, organizational cynicism was found to fully mediate these relationships. This study implies the need for the government and healthcare management commitments against abusive supervision in the healthcare system.